Government Strategies On Co-Operatives During The Covid-19 Pandemic In Supporting Economic Resilience - Dalimunthe, Anantha Andhikatama; Suwito; Tumanggor, Muliahadi; Asmoro, Novky (Yayasan Pendidikan Belajar Berdikari, 2023)
Pandemic disease outbreaks are one of the non-physical non-military threats with a public safety dimension, when the covid-19 pandemic that occurred in early 2020 affected the world economy as well as in Indonesia, one of the affected sectors was the Cooperative, especially regarding finance. This study uses Lykke's strategy theory which includes 3 (three) aspects of Ends (Purpose) explaining